"On Water" promoted N-arylation reactions using Cu (0)/myo-inositol catalytic system. Issue 29 (18th July 2019) - Zhou, Qifan; Du, Fangyu; Chen, Yuanguang; Fu, Yang; Chen, Guoliang
Graphical abstract: Highlights: Myo-inositol, a cardiovascular medicine, was used as tridentate O -donor ligand for Cu-catalyzed amination reaction in water. The CN coupling reaction of aryl halides with amines were achieved by Cu powder/myo-inositol catalytic system. The broad scope of substrates was participated in the coupling. Abstract: Myo-inositol is originally applied as a cardiovascular medicine in clinic, which can be multi-ton manufactured via extraction from the byproducts in agricultural product processing such as defatted rice bran and corn-soaking water. Herein, the application of myo-inositol (MI) as a novel versatile tridentate O -donor ligand has been first described for promoting Cu-catalyzed amination reaction in aqueous medium.